2019
DOI: 10.1136/bmjdrc-2018-000606
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endothelial function and sympathetic nervous system activity along the glucose continuum in individuals with differing metabolic risk profiles and low dietary sodium intake

Abstract: Objective: Low sodium intake may trigger sympathetic nervous system (SNS) activation and endothelial dysfunction. Studies have not explored these associations along the glucose continuum. Accordingly, we compared endothelial function and SNS activity in individuals with low sodium intake and differing categories of metabolic risk along the glucose continuum. We hypothesized that low sodium intake is associated with (1) impairment of endothelial function and (2) higher SNS activity in individuals with higher me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Of the articles reviewed herein, five showed differences in RH between healthy subjects and diabetic patients with and/or without neuropathy [15,30,33,57,58], while one study did not show such differences between healthy subjects and diabetic patients, but patients with diabetic ulcers had lower RH index values compared to healthy controls [59]. Another study found no significant difference in blood flow after a muscle strain that induced reactive hyperemia (PSRH) between normal subjects and diabetic non-smokers [43].…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Of the articles reviewed herein, five showed differences in RH between healthy subjects and diabetic patients with and/or without neuropathy [15,30,33,57,58], while one study did not show such differences between healthy subjects and diabetic patients, but patients with diabetic ulcers had lower RH index values compared to healthy controls [59]. Another study found no significant difference in blood flow after a muscle strain that induced reactive hyperemia (PSRH) between normal subjects and diabetic non-smokers [43].…”
Section: Resultsmentioning
confidence: 98%
“…Diabetic autonomic neuropathy (DAN) is a complicated heterogeneous disorder that affects the autonomic neurons of the peripheral nervous system [12]. Subclinical autonomic dysfunction can occur within 1-2 years of the diagnosis of diabetes mellitus [11,[13][14][15], and patients remain asymptomatic until well after the onset of diabetes [9,11,13,14]. Poor glycemic control, older age, a longer duration of diabetes, female gender, and obesity are major risk factors for the development and progression of this disease [12].…”
Section: Diabetic Autonomic Neuropathymentioning
confidence: 99%
See 2 more Smart Citations
“…The interconnection between T2DM and endothelial dysfunction has been established a long time ago, with the latter representing an initial step towards the development and progression of cardiovascular disease [2]. Recent data suggest that patients with T2DM feature an impaired endothelial function, even in the context of well-controlled cardio-metabolic risk factors and low sodium intake, compared to normal and impaired glucose tolerance subjects [3].…”
mentioning
confidence: 99%